Evaluation of the 10-11 Year Age Group (Ku-4) Swimming Achievement Program in the Swimming School of Bangkalan District - Andryan Dwi Kusuma Putra; Yoso Wiyarno; Ujang Rohman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to evaluate the Swimming Achievement Program Development for Age Group 10-11 Years (AG-4) at the Bangkalan Swimming School (SRB). The research is motivated by the achievement results of the athletes, which are still fluctuating or unstable. Specifically, athletes in Age Group 4 (AG-4), aged 10–11 years, have not yet obtained significant achievements.The research model employed is the CIPP (Context, Input, Process, Product) evaluation model (evaluation research). This study is focused specifically on evaluating the Swimming Achievement Program for Age Group 10-11 Years (AG-4) at the Bangkalan Swimming School (SRB). The data collection technique utilized is quantitative, obtained through the distribution of questionnaires to the management, coaches, and athletes of Age Group 10-11 Years (AG-4) at the Bangkalan Swimming School.The research findings indicate that the overall evaluation of the SRB achievement development program for the Age Group 10-11 Years (AG-4) falls into the moderate criterion with a total score of 3.14. Furthermore, the study identifies several fundamental and important points that must be considered by the Bangkalan Swimming School (SRB) management to determine the future sustainability of the program.Based on the CIPP indicators, the Context (program background) scored 3.17 (moderate category), the Input (human resources) scored 3.10 (moderate category), the Process (program implementation) scored 3.16 (moderate category), and the Product (achievement) scored 3.15 (moderate category).In conclusion, based on the research results and data analysis conducted, the evaluation of the Bangkalan Swimming School (SRB) achievement development program for the Age Group 10-11 Years (AG-4) received a score of 3.16, which is categorized as moderate.